Rice Production in Tidal Lands: The Role of Several Soil Properties (Journal of Wetlands Environmental Management, 2024)
Tidal swamp land is an alternative land that has great potential for agricultural development in the future. At present time, the rice productivity in tidal areas vary from relatively high to low. This diversity is caused by obstacles and problems, including low soil fertility, acidic soil reactions, the presence of pyrite, high levels of Al, Fe, Mn and organic acids, deficiency of P, poor base cations such as Ca, K, Mg, and suppressed microbial activity. This research aimed at determining the role of several soil properties (pH, soluble Fe, available P, organic C, soil CEC, presence of pyrite and groundwater level) on rice production in tidal areas. This research is field research using survey methods. Sampling in the field was carried out using purposive sampling technique, namely referring to differences in rice production of the Karang Dukuh variety in Barito Kuala Regency. Soil samples were taken at a depth of 0-20 cm from the ground surface three points at each location with different rice production level. The research results showed that only three variables had a partially significant effect on rice production, namely soil pH, soluble Fe and available P. Together these three variables play a major role in rice production in tidal areas which best (coefficient of determination of 0.919) approached with aquation Y ( rice production ) = 1,501 − 0.011 Fe-soluble + 0.269 P-available + 0.561 Soil pH. C-organic content, soil CEC, pyrite depth and water level play a very small role (≤ 8.1%) in rice production in tidal areas (coefficient of determination ≤ 0.081).